[OP.4A.01] CHANGES IN SUBCLINICAL TARGET ORGAN DAMAGE IN OBESE PATIENTS UNDERGOING BARIATRIC SURGERY. THE BARIHTA STUDY. (September 2017) - Oliveras, A.; Granados, A.M.; Vazquez, S.; Sans, L.; Alvarez, S.; Arias, C.; Ho, T.; Benaiges, D.; Fontdevila, L.; Faura, A.; Ramon, J.M.; Goday, A.; et al.
Abstract : Objective: We aimed to assess changes in subclinical target organ damage (STOD) in obese patients 1 month after BxS. Design and method: We conducted a prospective study of obese patients undergoing BxS, either gastric bypass or sleeve gastrectomy. Office-BP and 24h-ambulatory-BP, both peripheral and central, were measured by the portable automated Mobile-O-Graph® device at baseline and 1 month after BxS. Changes in markers of STOD such as arterial stiffness (as measured by 24h-pulse wave velocity [PWV], 24h-augmentation index [AIx] and pulse pressure [PP]), and urinary albumin excretion (UAE) were evaluated. Results: Thirty-five patients scheduled for BxS (77% women; mean age: 41.5 ± 9.7 yr; body weight: 119 ± 22 Kg; body mass index, median [IQR]: 41.1 Kg/m 2 [38.2; 46, 1]; hypertensives: 49%) were consecutively included and prospectively evaluated. Arterial stiffness changed at 1 month follow-up [mean (95%CI)]: variation of 24h-PWV = −0.21 (−0.31 to −0.10), p < 0.001; variation of 24h-AIx = −2.39 (−3.99 to −0.79), p = 0.005; variation of 24h-peripheral-PP = −3.6 (−5.4 to −1.7), p < 0.001; variation of 24h-central-PP = −3.8 (−5.4 to −2.1), p < 0.001. Albuminuria also changed significantly: baseline UAE, median [IQR] = 4.3 [2.9; 12.1]; 1-month UAE = 5.1 [3.3; 7.6]; Z −2.4; p = 0.018. Body weight (Kg) variation (median [IQR]) was: baseline = 115 [101; 139]; 1-month = 104 [89; 122]; Z −5.1; p < 0.001. Generalized linear models were built to assess changes in STOD after adjusting by age, gender, hypertensive condition, variation of 24h-peripheral SBP, variation of body weight and the corresponding baseline STOD value. Variation of PWV was associated with variation of 24h-SBP (p < 0.001, r2 = 0.850); variation of PP was associated with variation of 24h-SBP (p < 0.001, r2 = 0.670); variation of AIx was associated with age (p = 0.019), baseline AIx (p = 0.019) and marginally with variation of 24h-SBP (p = 0.09), r2 = 0.265; variation of UAE was associated with age (p = 0.005), gender (p = 0.008) and baseline UAE (p < 0.001) and marginally with variation of 24h-SBP (p = 0.051), r2 = 0.779. Conclusions: In obese patients, STOD decreased at 1 month following bariatric surgery. Arterial stiffness improvement was mostly due to changes in 24h-SBP, while albuminuria decrease was mostly depending on baseline albuminuria. Body weight loss per se was not responsible for STOD changes.